Treinamento auditivo acusticamente controlado em pacientes com neurofibromatose tipo 1 - Pollyanna Barros Batista (2016)
Introduction: Individuals with neurofibromatosis type 1 (NF1) often show auditory processing deficits related to their overarching language impairment. Auditory training (AT) acoustically controlled may potentially alleviate these deficits through training-induced improvements in auditory processing (AP). Objectives: Verify the efficacy of AT in NF1 patients with auditory processing disorder (APD) and verify the maintenance of auditory skills trained one year after the end of the intervention in this population. Methods: To assess the efficacy of AT on auditory function in individual with NF1, auditory behavioral tests performance (speech in noise - SN, staggered spondaic word - SSW, duration patterns - DP and gaps in noise - GIN) were collected from 2 groups (G1 individuals with NF1 and G2 individuals without NF1) who completed 8-week AT program and were revaluated after 12-weeks from the initial assessment. The G1 was revaluated after one-year that finish the AT to prove the maintenance of auditory training. This group was called G3. Statistical analysis was performed using the Mann-Whitney test to compare inter-group differences before and after training and the Wilcoxon test to verify intra-group differences. Statistical significance was set at p value 0.05. Results: The groups G1, G2 and G3 were composed of 22, 11 and 13 individuals, respectively. All participants presented normal auditory peripheral hearing, but altered central AP. The comparison between the evaluations made before and after the AT pointed a statistically significant result for SN right ear (RE) (p = 0.000), SN left ear (LE) (p = 0.004), SSW RE (p = 0.001), SSW LE (p = 0.000), GIN RE (p = 0.027) and GIN RE (p = 0,038), suggesting improvement in auditory closure, figure-ground and temporal resolution abilities, respectively. No improvements were observed in PD humming (p = 0.073) and PD labeling (p = 0.572). Comparisons between G1 and G2 indicate that the groups were similar before the intervention and remained similar after AT, except for the DP humming test (p = 0.013). It was observed in G3 that trained auditory skills were maintained one year after the end of the AT. Conclusions: These results provide an indication of the efficacy of training in auditory closure, figure-ground and auditory resolution abilities, and that these benefits keep one year after the end of the AT.